THE RELEVANCE OF QAWAID TAFSIR IN UNDERSTANDING THE QUR'AN - Khodijah, Siti; Aswadi, Aswadi (Jurnal Al I'jaz, 2024)
This research discusses in-depth qawa‘id tafsir as the main methodological in the interpretation of the Qur’an, focusing on how these principles support an accurate and contextual understanding of the sacred text. This research uses a type of library research which is presented using a qualitative research model with descriptive method and by using sources from classical to contemporary books. The results show that qawa‘id tafsir not only serves as a technical guide in interpreting Qur’anic verses but also plays an essential involvement in ensuring that interpretations remain relevant and in accordance with the objectives of the shari’ah. This article describes the evolution of qawa‘id tafsir over time, from early discussions in classical works to significant contributions in contemporary literature, which enrich the methodological framework and understanding of tafseer. Through an in-depth understanding of the definition, history, and significance of qawa‘id tafsir, this article highlights how these rules help mufassir to face interpretive challenges in the modern era, as well as ensure consistent and applicable interpretations in evolving social, legal, and cultural contexts. Qawa‘id tafsir serves as a bridge that connects the Qur’anic text with the needs of the times, making it an essential tool in maintaining the purity and relevance of the divine message in the Qur’an.